If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 = (16) + -1(4x) 28 = 16 + -1(4x) Remove parenthesis around (4x) 28 = 16 + -1 * 4x Multiply -1 * 4 28 = 16 + -4x Solving 28 = 16 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 28 + 4x = 16 + -4x + 4x Combine like terms: -4x + 4x = 0 28 + 4x = 16 + 0 28 + 4x = 16 Add '-28' to each side of the equation. 28 + -28 + 4x = 16 + -28 Combine like terms: 28 + -28 = 0 0 + 4x = 16 + -28 4x = 16 + -28 Combine like terms: 16 + -28 = -12 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| 3x(20-x)= | | -3+1=4*3-5-3*3 | | -14x+7y=-21 | | y-16=.25 | | -9x+30=-12 | | 8y^2+6y-35=0 | | -x-5=-2 | | X+(2X)+(X+2ft)=70 | | 10m+5=5 | | -x-2=-5 | | 9-2x=6x-15 | | 3(x-0.5x)-2x=132 | | .33=h+.4 | | 165u-4= | | 68-2x=79-3x | | t-23.5=39.7 | | 36=(8)-(14x) | | 0.05m=13.80 | | 9.2=-5g-23.3 | | (-3x)-(7)=23 | | 65-x=180 | | 9+2x=49 | | (-3x)-(7)=3 | | [5x]-7=14 | | abs(5x-4)=-6 | | 9x-4=72 | | 15m+6.3=9.8 | | abs(5x-4)=6 | | Y=7.5+0.5x | | 12y=-48+4x | | 4+12x=112 | | 2(3x+1)-x=3 |